2016
DOI: 10.4274/cayd.36035
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Poisoning Cases Our Followed in Pediatric Intensive Care Unit

Abstract: Zehirlenmeler çocuk yoğun bakım üniteleri ve hastane yatışlarında önlenebilir morbidite ve mortalitenin önemli bir kısmını oluşturmakla beraber yoğun bakım gerektiren zehirlenmeler hakkında bilgi sınırlıdır. Bu çalışmada Erciyes Üniversitesi Tıp Fakültesi Çocuk Yoğun Bakım Ünitesi'nde tedavi edilen zehirlenme olgularının değerlendirilmesi amaçlanmıştır. Yöntemler: 2009-2015 yılları arasında akut zehirlenme nedeniyle yoğun bakım ünitesine kabul edilen 186 hastanın kayıtları geriye dönük olarak incelendi. Bulgul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
3
4
2
1
Order By: Relevance
“…In studies, the average length of stay in the PICU for poisoning cases was reported to be between 1.2 and 2.8 days. [21][22][23] In our study, the average length of stay was 1.6 ± 1.3 days, which was comparable to the literature.…”
Section: Discussionsupporting
confidence: 89%
“…In studies, the average length of stay in the PICU for poisoning cases was reported to be between 1.2 and 2.8 days. [21][22][23] In our study, the average length of stay was 1.6 ± 1.3 days, which was comparable to the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Poisoning cases occur because of accidents between the ages of 0-5, and for suicide in adolescence. Suicidal poisoning rate was reported by Ulu et (16,23,29). In the present study, this rate was 9.5%.…”
Section: Discussionsupporting
confidence: 60%
“…It was determined in the present study that 38.47% were followed in the emergency clinic and ward, and 16.72% in the pediatric health and diseases ward. When evaluated in terms of hospitalization rate of the poisoning cases in the Intensive Care Units, Ozdemir et al reported it as 25.3%; Araz et al 14.7%; Ulu et al 6.1%, and Tekerek et al 5.4% (10,16,18,29,30). In the present study, the rate of hospitalization in the Intensive Care Units was found to be 1.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are showing that suicidal poisonings are more common in adolescent girls [13,14]. In the study of Tekerek et al [15], suicidal poisonings were frequently seen in girls and accidental poisonings were frequently seen in boys, whereas most of the poisonings were seen to be accidental. In the literature, suicidal poisoning cases increase with age.…”
Section: Resultsmentioning
confidence: 99%